2020
DOI: 10.1111/acps.13175
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiome and inflammation in obsessive‐compulsive disorder patients compared to age‐ and sex‐matched controls: a pilot study

Abstract: The gut microbiome and inflammation in obsessive-compulsive disorder patients compared to age-and sex-matched controls: a pilot study. Objective: To compare the gut microbiome profile (by way of taxon analysis and indices of band a-diversity) and inflammatory markers (C-reactive protein [CRP], interleukin-6[IL-6] and tumour necrosis factor-a [TNF-a]) of obsessive-compulsive disorder (OCD) outpatients and non-psychiatric community controls. Methods: We collected morning stool and blood samples from 21 nondepres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 52 publications
5
55
4
Order By: Relevance
“…Several researchers have speculated that the microbiome might also play a role in the development of OCD (Rees, 2014; Turna et al, 2016). In fact, a recent pilot study of the gut microbiome in OCD has observed some dysbiosis in OCD cases compared to controls (Turna et al, 2020), and a previous work observed a difference in gut microbial composition in deer mice presenting an obsessive behavior compared to the normal individuals (Scheepers et al, 2019), while microbial treatments such as germ-free environment and probiotic treatments can modify OCD-like behavior in rodents (Bastiaanssen et al, 2019), and some OCD risk factors, such as stress, pregnancy or antibiotic use, are known to disrupt the gut microbiome (Rees, 2014). Moreover, it is recognized that some children, after suffering a streptococcal infection, present with a sudden onset of tics, OCD and other behavio r al symptoms, a condition known as pediatric autoimmune neuropsychiatric disorders associated with streptococcal infections syndrome (PANS/PANDAS) (Snider and Swedo, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have speculated that the microbiome might also play a role in the development of OCD (Rees, 2014; Turna et al, 2016). In fact, a recent pilot study of the gut microbiome in OCD has observed some dysbiosis in OCD cases compared to controls (Turna et al, 2020), and a previous work observed a difference in gut microbial composition in deer mice presenting an obsessive behavior compared to the normal individuals (Scheepers et al, 2019), while microbial treatments such as germ-free environment and probiotic treatments can modify OCD-like behavior in rodents (Bastiaanssen et al, 2019), and some OCD risk factors, such as stress, pregnancy or antibiotic use, are known to disrupt the gut microbiome (Rees, 2014). Moreover, it is recognized that some children, after suffering a streptococcal infection, present with a sudden onset of tics, OCD and other behavio r al symptoms, a condition known as pediatric autoimmune neuropsychiatric disorders associated with streptococcal infections syndrome (PANS/PANDAS) (Snider and Swedo, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…103 Interestingly, a recent Canadian study was the first to show that adult OCD patients have less richness/ evenness of gut microbiota compared to controls and in particular they display a lower presence of three butyrateproducing genera (namely Oscillospira, Odoribacter, and Anaerostipes). 95 These latter results are of special interest since butyrate-producing species seem to have an antiinflammatory effect on human immunological state. 95 To the best of our knowledge, there are still no available trials on probiotics interventions for OCD patients.…”
Section: Minocyclinementioning
confidence: 97%
“…95 These latter results are of special interest since butyrate-producing species seem to have an antiinflammatory effect on human immunological state. 95 To the best of our knowledge, there are still no available trials on probiotics interventions for OCD patients. Only studies on animal models of OCD and on healthy volunteers with OC symptoms showed intriguing results.…”
Section: Minocyclinementioning
confidence: 97%
See 1 more Smart Citation
“…In addition, B. breve 1205 reduced anxiety as assessed by the elevated plus maze, and B. longum 1714 exerted antidepressant-like effects based on the tail suspension test [ 87 ]. Turna et al reported that OCD patients exhibited showed lower species richness/evenness and a relatively low abundance of butyrate-producing genera ( Oscillospira , Odoribacter , and Anaerostipes ) compared to healthy controls using 16S rRNA microbiota sequencing analysis performed on samples from 21 OCD patients and 21 healthy controls [ 88 ]. Table 5 summarizes the main characteristics of these trials.…”
Section: Microbiome Research In Psychiatric Disordersmentioning
confidence: 99%